Judicial Overview On Criminal Liability Against A Person Who Deliberately Use, Sell Or Export An Industrial Design Without Getting Approval From The Exclusive Rightholders Of Industrial Design Based On Industrial Design Law - Akbar Sigratama; Erlina B; Melisa Safitri (Universitas PGRI Madiun, 2021)
Industrial design is a part of the intellectual property created by tasteful and corrosive thought and imagination. Protection against industrial design was indispensable to the certainty of laws to designers. This research issue to find out how the protection of industrial design that has conforms to industry design is listed in the general list under the 31st year 2000 act. This method of research USES the yuridis normatif and empirical approaches. The type of data used is secondary and primary data. The study concluded that a designer who lists industrial design products in the registry, has the exclusive rights granted to him by the republic of Indonesia. It can forbid anyone without his consent to use, sell, manufacture, export, import. When using bad faith, as holders of exclusive rights may file a civil suit and/or criminal charges. The conclusion is that the industrial design that industrial design could provide with the design of science-based on the design of science-based, should fill with novelty of that industry's design and yet no public announcement was made